Separation membrane as well as preparation method and application thereof
By adopting support layer, intermediate layer and functional layer structures in the CO2 separation membrane and using amino polymer to enhance the performance of the intermediate layer, the existing membrane has solved the problem of taking into account both flux and selectivity, achieving efficient CO2 separation effect, while simplifying the process and improving environmental protection.
Patent Information
- Application Number
- CN202311334880.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-16
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-10-16
AI Technical Summary
The existing CO2 separation membranes have challenges in both high gas flux and selectivity, and the preparation process is complex and not environmentally friendly.
A support layer, an intermediate layer and a functional layer structure are sequentially stacked, wherein the intermediate layer is made of amino polymer, and an intermediate layer is prepared by polymerization on the surface of the support layer, and an interfacial polymerization is performed thereon.
It achieves the separation selectivity between high CO2 flux and high CO2 and N2, and is simple and environmentally friendly, suitable for large-scale production.
Smart Images

Figure CN119838431A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of membrane separation materials, and in particular to a separation membrane, a preparation method thereof, and application thereof in CO2 separation. Background Art
[0002] Since the Industrial Revolution, the burning of large amounts of fossil fuels has caused the concentration of CO2 in the atmosphere to increase by nearly 50%, and this is expected to continue to rise. The emission of greenhouse gases such as CO2 is the main cause of global warming. As energy and environmental issues become increasingly severe, reducing greenhouse gas emissions and improving carbon utilization efficiency have become hot topics of concern to the international community today. Therefore, separating and recovering CO2 from emission sources and adopting certain methods to achieve CO2 conversion and utilization have become the focus of scientific and technological research at home and abroad. CO2 separation membrane technology has attracted widespread research interest due to its advantages such as simple equipment, low fixed investment and low energy consumption. Currently, CO2 separation membranes prepared from a single polymer are generally difficult to achieve both high selectivity and permeability. Compared with homogeneous membranes, thin-layer composite membrane structures have a porous layer to provide mechanical support, which can significantly reduce the thickness of the effective selective layer above, thereby reducing the overall mass transfer resistance and achieving higher flux.
[0003] To ensure low mass transfer resistance, the gas flux of the lower porous support layer should be at least 10 times that of the effective selective separation layer above, ensuring that the majority (over 90%) of the transmembrane resistance lies within the separation layer. However, during the preparation of the separation layer by methods such as coating, deposition, or interfacial polymerization, the presence of pores on the support layer's surface inevitably causes some of the diluted polymer solution to penetrate the porous structure and clog the pores. This not only significantly increases the effective thickness of the selective layer in the resulting composite membrane, reducing the membrane's permeability, but also easily causes surface defects on the membrane, affecting the membrane's gas selectivity. To prevent this unfavorable permeation phenomenon, an intermediate layer is often added between the selective layer and the porous support layer.
[0004] Currently, the most commonly used materials for preparing the intermediate layer are rubbery, highly permeable polymers such as polydimethylsiloxane (PDMS) and poly-1-(trimethylsilyl)-1-propyne (PTMSP). The CO2 permeability of these silicone rubbers can reach a maximum of approximately 19,000 to 37,000 barrers, but the permeability of their coatings rapidly decreases due to aging. For example, the CO2 permeability of a PTMSP composite membrane coated on a polyacrylonitrile (PAN) support can decrease by 80% within 14 days (Dai Z, Ansaloni L, Deng L. Green Energy and Environment: English Edition, 2016, 000(002), p: 102-128). Post-crosslinking these coatings can improve the stability of the permeation flux, but the steps involved are more complex. Furthermore, the preparation of silicone rubber coatings requires the use of large amounts of organic solvents and high and low temperature conditions.
[0005] CN104428050A discloses a gas separation membrane having a cross-linked dialkylsiloxane in an intermediate layer and a preparation method thereof. However, the thermal cross-linking or ultraviolet cross-linking reaction requires one or more organic solvents and the addition of an initiator and a catalyst. Therefore, the method is not gentle and environmentally friendly, and cross-linking will reduce the permeability of the membrane.
[0006] CN113631245A discloses a method for preparing a membrane for separating acidic gases such as CO2 from mixed gases. The method includes adding dispersed nanoparticles to an intermediate layer matrix, which can improve the aging of the polymer. However, the compatibility between inorganic nanoparticles such as silica and the matrix is poor, which is not conducive to achieving reliable membrane mechanical strength and stable operation.
[0007] The existing silicone rubber intermediate layer has problems such as complicated preparation process, solvent pollution, and unstable membrane performance. Therefore, it is of great significance to provide a separation membrane with a simple and environmentally friendly preparation method. Summary of the Invention
[0008] The purpose of the present invention is to overcome the problem that the existing separation membrane in the prior art cannot simultaneously improve gas flux and selectivity, and to provide a separation membrane and its preparation method and application. The separation membrane has both a high CO2 flux and a high separation coefficient between CO2 and N2, and the preparation process is simple and green and environmentally friendly.
[0009] To achieve the above objectives, the present invention provides a separation membrane in a first aspect, wherein the separation membrane comprises a support layer, an intermediate layer and a functional layer stacked in sequence; wherein the material of the intermediate layer comprises an amino polymer.
[0010] A second aspect of the present invention provides a method for preparing a separation membrane, wherein the method comprises:
[0011] (1) in the presence of an additive, polymerizing a reaction solution containing dopamine or dopamine and an amino group-containing reactant on the surface of a support layer to prepare an intermediate layer containing an amino polymer;
[0012] (2) The separation membrane is obtained by performing interfacial polymerization reaction on the intermediate layer by the oil phase monomer in the oil phase solution and the water phase monomer in the water phase solution.
[0013] The third aspect of the present invention provides a separation membrane prepared by the aforementioned preparation method.
[0014] A fourth aspect of the present invention provides an application of the aforementioned separation membrane in CO2 separation.
[0015] Through the above technical solution, the present invention has the following beneficial effects:
[0016] (1) In the present invention, non-covalent interactions allow the sequentially stacked support layer, intermediate layer, and functional layer to adhere closely to each other, thereby increasing the gas flux of the separation membrane and enabling selective separation of CO2. Specific amino polymers further promote the selective transfer of CO2, increasing the rate at which CO2 permeates the membrane relative to other gases, thereby achieving selective separation of CO2.
[0017] (2) The preparation method of the present invention first prepares an intermediate layer on the support layer, and then prepares a functional layer on the intermediate layer; the specific preparation method allows the prepared support layer, intermediate layer and functional layer to be connected to each other through van der Waals forces; further, the specific method makes the intermediate layer smooth and flat, providing an excellent location for preparing the functional layer, facilitating the interfacial polymerization reaction and increasing the reaction rate;
[0018] (3) The process of the present invention is simple, environmentally friendly, and can be produced on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Schematic diagram of the structure of the separation membrane of Example 1 of the present invention;
[0020] Figure 2 This is an electron microscope image of a cross section of the separation membrane of Example 1. DETAILED DESCRIPTION
[0021] The endpoints of the ranges and any values disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered to be specifically disclosed herein.
[0022] A first aspect of the present invention provides a separation membrane, wherein the separation membrane comprises a support layer, an intermediate layer, and a functional layer stacked in sequence;
[0023] Wherein, the material of the intermediate layer includes amino polymer.
[0024] In the present invention, the inventors found that the intermediate layer contains amino polymers, which enables the separation membrane to selectively pass gases that have affinity interactions with amino groups, thereby screening the gases and improving the selectivity of the gases. The separation membrane of the present invention can selectively separate CO2 and N2 gases.
[0025] In the present invention, the middle layer is relatively smooth, which is conducive to preparing the functional layer on its surface. The layers of membrane are stacked tightly, ensuring that the separation membrane has a higher gas flux.
[0026] According to the present invention, the N content in the amino polymer is 3-45 wt%.
[0027] In the present invention, the N content in the amino polymer is measured by X-ray photoelectron spectroscopy. When the N content meets the above range, it can effectively promote gas transfer and increase CO2 flux.
[0028] Furthermore, the N content in the amino polymer is 6-12 wt%.
[0029] According to the present invention, the theoretical weight average molecular weight of the amino polymer is 300-50000 Da, preferably 400-10000 Da.
[0030] According to the present invention, the amino polymer is selected from homopolymers and / or copolymers of dopamine.
[0031] In the present invention, the homopolymer and / or copolymer of dopamine has a high nitrogen content, which can effectively promote CO2 transfer and improve CO2 flux and gas selectivity.
[0032] According to the present invention, the amino polymer is selected from at least one of polydopamine, dopamine-ethylenediamine copolymer, dopamine-diethylenetriamine copolymer, dopamine-triethylenetetramine copolymer, dopamine-tetraethylenepentamine copolymer, dopamine-polyethyleneimine copolymer, dopamine-ethylenediamine-polyethyleneimine copolymer, dopamine-diethylenetriamine-polyethyleneimine copolymer, dopamine-triethylenetetramine-polyethyleneimine copolymer and dopamine-tetraethylenepentamine-polyethyleneimine copolymer; preferably at least one of polydopamine, dopamine-polyethyleneimine copolymer and dopamine-triethylenetetramine copolymer.
[0033] According to the present invention, the material constituting the support layer is at least one selected from polysulfone, polyethersulfone, polyacrylonitrile and polyvinylidene fluoride.
[0034] According to the present invention, the weight average molecular weight of the material constituting the support layer is 1000-500000 Da, preferably 2500-150000 Da.
[0035] According to the present invention, the support layer has a porous structure.
[0036] According to the present invention, the porosity of the support layer is >10%.
[0037] According to the present invention, the average pore size of the support layer is 1-10000 nm.
[0038] In the present invention, the porosity of the support layer is measured by a scanning electron microscope and the pore area in the field of view is divided by the total surface area. The average pore size of the support layer is measured by a scanning electron microscope and the average value is calculated.
[0039] In the present invention, the support layer with the porosity and average pore size meeting the above-mentioned specific ranges can allow gas to pass through, and the surface of the generated support layer is relatively smooth, which is conducive to preparing an intermediate layer on the surface and improving the degree of film adhesion.
[0040] Furthermore, the porosity of the support layer is 25-75%.
[0041] Furthermore, the average pore size of the support layer is 5-500 nm.
[0042] According to the present invention, the thickness of the support layer is 20-500 μm, the thickness of the intermediate layer is 10-500 nm, and the thickness of the functional layer is 10-1100 nm.
[0043] In the present invention, the separation membrane meeting the above thickness range has both high gas flux and gas selectivity.
[0044] Furthermore, the thickness of the support layer is 60-150 μm, the thickness of the intermediate layer is 50-300 nm, and the thickness of the functional layer is 50-400 nm.
[0045] According to the present invention, the average pore size of the separation membrane is 0.1-1 nm.
[0046] The average pore size of the separation membrane is tested according to the standard GB / T 42269-2022 "Test method for pore size of separation membranes - Gas permeation method". At the same time, the pore sizes of the support layer, intermediate layer and functional layer are different, and the smallest pore size among them is defined as the average pore size of the separation membrane. Different pore sizes can screen gas molecules of different sizes to achieve selective gas separation.
[0047] Furthermore, the average pore size of the separation membrane is 0.2-0.5 nm.
[0048] According to the present invention, the material constituting the functional layer is selected from at least one of polyamide and polyester.
[0049] In the present invention, the materials constituting the functional layer are conventional materials in the art and do not need to be limited as long as they can achieve the technical effects of the present invention. The unreacted -NH2 and -OH in the amino polymer on the intermediate layer are connected to the -NH2 and -O- in the material of the functional layer through non-covalent bonds such as hydrogen bonds and electrostatic interactions.
[0050] In the present invention, the polymer material in the functional layer has a high gas flux and a separation coefficient between CO2 and N2, and is suitable for CO2 gas separation.
[0051] According to the present invention, the CO2 flux of the separation membrane is ≥300 GPU.
[0052] According to the present invention, the separation selectivity of CO2 and N2 of the separation membrane is ≥20.
[0053] The separation membrane of the present invention can simultaneously have a high CO2 flux and a high selectivity, and is suitable for the gas separation of CO2 and N2.
[0054] Furthermore, the CO2 flux of the separation membrane is ≥400GPU.
[0055] Furthermore, the separation selectivity of the separation membrane between CO2 and N2 is ≥30.
[0056] A second aspect of the present invention provides a method for preparing a separation membrane, wherein the method comprises:
[0057] (1) in the presence of an additive, polymerizing a reaction solution containing dopamine or dopamine and an amino group-containing reactant on the surface of a support layer to prepare an intermediate layer containing an amino polymer;
[0058] (2) The separation membrane is obtained by performing interfacial polymerization reaction on the intermediate layer by the oil phase monomer in the oil phase solution and the water phase monomer in the water phase solution.
[0059] In the present invention, the "amino group-containing reactant" does not include dopamine.
[0060] The preparation method of the present invention first prepares an intermediate layer on the support layer, and then prepares a functional layer on the intermediate layer; the specific preparation method enables the prepared support layer, intermediate layer and functional layer to be connected to each other through non-covalent bond interactions; further, the specific method makes the intermediate layer smooth and flat, providing an excellent place for preparing the functional layer, facilitating the interfacial polymerization reaction, and improving the reaction rate.
[0061] At the same time, the inventors unexpectedly discovered that dopamine contains a large number of amino groups, which can promote the transfer of CO2, so that the prepared separation membrane has a higher CO2 flux; at the same time, the dopamine polymerization reaction is mild and the reaction conditions are simple, which is conducive to industrial promotion; and when dopamine is polymerized with reactants containing amino groups, the amino content in the middle layer can be increased, so that the separation membrane's promotion of CO2 transfer is enhanced, thereby increasing the CO2 flux and selectivity relative to other gases (such as N2, etc.).
[0062] According to the present invention, in step (1), an additive is added to adjust the pH to 7.5-10.
[0063] In the present invention, adjusting the pH to the above range can ensure smooth progress of the intermediate layer preparation reaction and avoid defects in the intermediate layer.
[0064] Furthermore, the pH is 8.5-10.
[0065] According to the present invention, the additive includes additive A, or additive A and additive B, the additive A is selected from sodium hydroxide and / or tris(hydroxymethyl)aminomethane, and the additive B is selected from at least one of hydrochloric acid, sodium dihydrogen phosphate and potassium dihydrogen phosphate.
[0066] According to the present invention, the amino group-containing reactant is selected from amino group-containing monomers and / or amino group-containing polymers.
[0067] According to the present invention, the amino group-containing monomer is at least one selected from ethylenediamine, diethylenetriamine, triethylenetetramine and tetraethylenepentamine.
[0068] According to the present invention, the amino group-containing polymer is selected from polyethyleneimine.
[0069] According to the present invention, the weight average molecular weight of the polyethyleneimine is 500-2000 Da, preferably 600-1800 Da.
[0070] In the present invention, the molecular weight of polyethyleneimine is relatively small, and when it is polymerized with dopamine, the reaction mechanism is similar to the reaction mechanism of dopamine with a monomer containing an amino group.
[0071] According to the present invention, the concentration of dopamine in the reaction solution is 0.1 wt%-5 wt%.
[0072] According to the present invention, in the reaction solution, the concentration of the amino-containing reactant is 0 wt % to 5 wt %.
[0073] In the present invention, the concentration of the amino-containing reactant in the reaction solution is 0 wt %, and the obtained product is a homopolymer of dopamine.
[0074] In the present invention, when the concentrations of dopamine and the amino-containing reactant meet the above-mentioned range, the prepared intermediate layer can be made smooth and flat, which is helpful for preparing the functional layer thereon. At the same time, the amino content in the prepared intermediate layer is relatively high, which promotes the transfer of CO2, so that the separation membrane has both a higher CO2 flux and gas selectivity of CO2 and N2.
[0075] Furthermore, in the reaction solution, the concentration of dopamine is 0.5 wt%-2 wt%.
[0076] Furthermore, in the reaction solution, the concentration of the amino-containing reactant is 0.2 wt%-2 wt%.
[0077] According to the present invention, when dopamine and the amino-containing reactant undergo polymerization reaction, the weight ratio of the dopamine to the amino-containing reactant is 1:10 or less.
[0078] In the present invention, when the weight ratio of the dopamine to the amino group-containing reactant satisfies the above range, the prepared intermediate layer can be made smooth and flat, while improving the CO2 flux and the selectivity of CO2 and N2.
[0079] Furthermore, when dopamine and the amino-containing reactant undergo a polymerization reaction, the weight ratio of the dopamine to the amino-containing reactant is 1:1.5 or less.
[0080] According to the present invention, the reaction time of the polymerization reaction is 2-48 hours, and the reaction temperature of the polymerization reaction is 0-50°C.
[0081] In the present invention, when the above-mentioned polymerization reaction time and temperature conditions are met, the obtained intermediate layer is smooth and flat, which is conducive to modifying the functional layer on its surface. At the same time, the reaction conditions are relatively mild and can be promoted on a large scale industrially.
[0082] Furthermore, the reaction time of the polymerization reaction is 5-24 hours, and the reaction temperature of the polymerization reaction is 20-35°C.
[0083] According to the present invention, in the aqueous phase solution, the concentration of the aqueous phase monomer is 1 wt%-4 wt%.
[0084] According to the present invention, in the oil phase solution, the concentration of the oil phase monomer is 0.05 wt%-0.5 wt%.
[0085] In the present invention, the aqueous phase monomers and oil phase monomers that meet the above ranges can make the prepared functional layer thinner and more compact, so that the prepared functional layer has higher CO2 flux and gas separation properties of CO2 and N2.
[0086] Furthermore, in the aqueous phase solution, the concentration of the aqueous phase monomer is 2 wt%-4 wt%.
[0087] Furthermore, in the oil phase solution, the concentration of the oil phase monomer is 0.05 wt%-0.15 wt%.
[0088] According to the present invention, the weight ratio of the aqueous phase monomers to the oil phase monomers is 2-40:1.
[0089] In the present invention, the aqueous phase monomer and the oil phase monomer satisfying the above weight ratio can make the reaction proceed more smoothly, thereby obtaining the aforementioned functional layer without causing waste of raw materials. The prepared functional layer enables the separation membrane to have higher gas flux and gas selectivity.
[0090] Furthermore, the weight ratio of the aqueous phase monomer to the oil phase monomer is 5-15:1.
[0091] According to the present invention, the oil phase monomer is selected from at least one of trimesoyl chloride, isophthaloyl chloride, 1,4-dichlorobenzyl and 3,3,4,4-biphenyltetrachloro. Preferably, it is trimesoyl chloride.
[0092] According to the present invention, the aqueous phase monomer is selected from amino compounds and / or hydroxyl compounds.
[0093] According to the present invention, the amino compound is selected from at least one of m-phenylenediamine, piperazine, ethylenediamine, triethylenetetramine, tetraethylenepentamine, 1,4-cyclohexanediamine, 1,3-diamino-2-methylpropane, bis(2-aminoethyl) ether, ethylene glycol bis(2-aminoethyl) ether, diethylene glycol di(3-aminopropyl) ether, 1,4-butanediol bis(3-aminopropyl) ether and 1,4-bis(3-aminopropyl)piperazine, preferably selected from m-phenylenediamine and / or piperazine.
[0094] According to the present invention, the hydroxy compound is selected from at least one of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin, preferably β-cyclodextrin.
[0095] According to the present invention, the oil phase solution further comprises an oil phase solvent, and the oil phase solvent is selected from at least one of n-hexane, n-heptane and isoparaffin.
[0096] According to the present invention, the isoparaffin is selected from Iospar G and / or Isopar E, both of which are solvent oil products of ExxonMobil.
[0097] According to the present invention, the interfacial polymerization reaction is carried out for 0.5-60 minutes at a temperature of 15-50°C.
[0098] In the present invention, the interfacial polymerization reaction meeting the above range has a faster reaction speed, milder reaction conditions, simpler process, and the prepared functional layer is thinner and defect-free, which is conducive to gas passage and improves gas flux.
[0099] Furthermore, the interfacial polymerization reaction time is 0.5-3 minutes, and the temperature is 25-50°C.
[0100] According to the present invention, step (1) further comprises: washing the prepared amino polymer intermediate layer with water.
[0101] In the present invention, the method of washing with water is not particularly limited and can be any common cleaning method in the art, preferably immersion, shaking and ultrasound, as long as the unreacted reactants on the surface are washed away.
[0102] In the present invention, the purpose of cleaning the intermediate layer is to remove polymers not attached to the surface, thereby making the intermediate layer smooth and free of impurities.
[0103] According to the present invention, the cleaning time is ≥5h, preferably ≥12h.
[0104] In the present invention, the ratio of the reaction solution containing dopamine or dopamine and amino-containing reactants to the membrane area of the support layer is 0.5-5 g / cm 2 .
[0105] In the present invention, the ratio of the oil phase solution to the membrane area of the intermediate layer of the separation membrane is 0.05-0.35 g / cm 2 .
[0106] In the present invention, the ratio of the aqueous phase solution to the middle membrane area of the separation membrane is 0.05-0.35 g / cm 2 .
[0107] The third aspect of the present invention provides a separation membrane prepared by the aforementioned preparation method.
[0108] A fourth aspect of the present invention provides an application of the aforementioned separation membrane in CO2 separation.
[0109] The present invention will be described in detail below through examples.
[0110] In the following examples and comparative examples,
[0111] The CO2 flux is measured by the differential pressure method. The specific method of the differential pressure method is in accordance with GB / T 1038.1-2022 "Plastic film and sheeting gas permeability test method Part 1: Differential pressure method";
[0112] The calculation formula of the separation coefficient of CO2 and N2 is: separation coefficient of CO2 and N2 = flux of CO2 / flux of N2;
[0113] The thickness of each layer in the separation membrane is measured as follows: the thickness of the support layer is measured using a spiral micrometer in the dry state, and the average value is calculated at 5 points with an accuracy of 1 μm; the thickness of the intermediate layer is the transition part in the SEM image (such as the attached Figure 1 The thickness of the functional layer is the distance from the top surface of the entire membrane to the boundary of the support layer in the SEM image minus the thickness of the intermediate layer, accurate to 1 nm.
[0114] The average pore size of the separation membrane is determined by the following method: testing in accordance with the standard GB / T 42269-2022 "Test method for pore size of separation membranes - Gas permeation method".
[0115] Polysulfone, weight average molecular weight 3500Da, purchased from Solvay;
[0116] Dopamine, purchased from Sigma-Aldrich;
[0117] Polyethyleneimine, weight average molecular weight 600Da, purchased from Sigma-Aldrich;
[0118] Triethylenetetramine, m-phenylenediamine, trimesoyl chloride, the purchasing company is Anaiji Chemical;
[0119] Sodium hydroxide, purchased by Sinopharm Reagent.
[0120] The support layer is polysulfone, and the preparation method is to add 400g of polysulfone to 1600g of dimethylacetamide to prepare a 20wt% solution, heat it to 75°C, wait for the solution to be uniform, coat it on a non-woven fabric substrate, and obtain the polysulfone support layer by phase inversion method, wherein the weight average molecular weight of the polysulfone is 3600Da.
[0121] Example 1
[0122] (1) At 25°C, tris(hydroxymethyl)aminomethane aqueous solution, 0.5 mol / L sodium hydroxide aqueous solution and 0.5 mol / L hydrochloric acid aqueous solution were added and the pH was adjusted to 8.5 by titration, and the total mass of the aqueous solution was 200 g. 2 g of dopamine was added and 324 cm 2 The polysulfone support layer is spread flat in a container and completely immersed in the mixed solution to carry out polymerization reaction for 24 hours. After the reaction, the residual liquid is drained and the membrane is thoroughly washed with water to obtain a membrane A1 with an intermediate layer laminated on the support layer;
[0123] (2) At 25°C, add 2 g of m-phenylenediamine to 98 g of water, add 0.15 g of trimesoyl chloride to 99.85 g of n-hexane, and 2 Interfacial polymerization reaction was carried out on the membrane A1 for 3 min, and the residual solvent was fully washed with water after the reaction to obtain separation membrane B1;
[0124] The film section of Example 1 was tested by electron microscopy. Figure 2 As shown, it can be seen from the electron microscope image that the intermediate layer is smooth and flat, and there is no clear boundary between the intermediate layer and the functional layer, which proves that the intermediate layer and the functional layer are closely fitted.
[0125] Example 2
[0126] (1) At 25°C, add tris(hydroxymethyl)aminomethane aqueous solution, 0.5 mol / L sodium hydroxide aqueous solution and 0.5 mol / L hydrochloric acid aqueous solution to adjust the pH to 10 by titration, and make the total mass of the aqueous solution 200 g, add 2 g of dopamine, and add 324 cm 2 The polysulfone support layer is spread flat in a container and completely immersed in the mixed solution to carry out polymerization reaction for 5 hours. After the reaction, the residual liquid is drained and the membrane is thoroughly washed with water to obtain a membrane A2 with an intermediate layer laminated on the support layer;
[0127] (2) At 25°C, add 2 g of m-phenylenediamine to 98 g of water and 0.15 g of trimesoyl chloride to 99.85 g of n-hexane. 2 An interfacial polymerization reaction was carried out on A2 with a reaction time of 3 min. After the reaction, the residual solvent was fully washed with water to obtain a separation membrane B2.
[0128] Example 3
[0129] (1) At 25°C, add tris(hydroxymethyl)aminomethane aqueous solution, 0.5 mol / L sodium hydroxide aqueous solution and 0.5 mol / L hydrochloric acid aqueous solution to adjust the pH to 8.5 by titration, and make the total mass of the aqueous solution 200 g, add 2 g of dopamine and 3 g of polyethyleneimine, and add 324 cm 2The polysulfone support layer is spread flat in a container and completely immersed in the mixed solution to carry out polymerization reaction for 24 hours. After the reaction, the residual liquid is drained and the membrane is thoroughly washed with water to obtain a membrane A3 with an intermediate layer laminated on the support layer;
[0130] (2) At 25°C, add 2 g of m-phenylenediamine to 98 g of water, add 0.15 g of trimesoyl chloride to 99.85 g of n-hexane, and 2 Interfacial polymerization reaction was carried out on membrane A3 with a reaction time of 3 min. After the reaction, the residual solvent was fully washed with water to obtain separation membrane B3.
[0131] Example 4
[0132] (1) At 25°C, add tris(hydroxymethyl)aminomethane aqueous solution, 0.5 mol / L sodium hydroxide aqueous solution and 0.5 mol / L hydrochloric acid aqueous solution to adjust the pH to 8.5 by titration, and make the total mass of the aqueous solution 200 g, add 2 g of dopamine and 0.4 g of triethylenetetramine, and add 324 cm 2 The polysulfone support layer is spread flat in a container and completely immersed in the mixed solution to carry out polymerization reaction for 5 hours. After the reaction, the residual liquid is drained and the membrane is thoroughly washed with water to obtain a membrane A4 with an intermediate layer laminated on the support layer.
[0133] (2) At 25°C, add 2 g of m-phenylenediamine to 98 g of water, add 0.15 g of trimesoyl chloride to 99.85 g of n-hexane, and 2 Interfacial polymerization reaction was carried out on membrane A4 with a reaction time of 3 minutes. After the reaction, the residual solvent was fully washed with water to obtain separation membrane B4.
[0134] Example 5
[0135] (1) At 25°C, add tris(hydroxymethyl)aminomethane aqueous solution, 0.5 mol / L sodium hydroxide aqueous solution and 0.5 mol / L hydrochloric acid aqueous solution to adjust the pH to 8.5 by titration, and make the total mass of the aqueous solution 200 g, add 2 g of dopamine and 0.4 g of ethylenediamine, and add 324 cm 2 The polysulfone support layer is spread flat in a container and completely immersed in the mixed solution to carry out polymerization reaction for 24 hours. After the reaction, the residual liquid is drained and the membrane is thoroughly washed with water to obtain a membrane A5 with an intermediate layer laminated on the support layer.
[0136] (2) At 25°C, add 2 g of m-phenylenediamine to 98 g of water, add 0.15 g of trimesoyl chloride to 99.85 g of n-hexane, and 2 Interfacial polymerization reaction was carried out on membrane A5 with a reaction time of 3 minutes. After the reaction, the residual solvent was fully washed with water to obtain separation membrane B5.
[0137] Example 6
[0138] (1) At 25°C, potassium dihydrogen phosphate buffer solution, 0.5 mol / L sodium hydroxide aqueous solution and 0.5 mol / L hydrochloric acid aqueous solution were added and the pH was adjusted to 7.4 by titration, and the total mass of the aqueous solution was 200 g. 2 g of dopamine was added and 324 cm 2 The polysulfone support layer is spread flat in a container and completely immersed in the mixed solution to carry out polymerization reaction for 24 hours. After the reaction, the residual liquid is drained and the membrane is thoroughly washed with water to obtain a membrane A6 with an intermediate layer laminated on the support layer.
[0139] (2) At 25°C, add 2 g of m-phenylenediamine to 98 g of water, add 0.15 g of trimesoyl chloride to 99.85 g of n-hexane, and 2 An interfacial polymerization reaction was carried out on the membrane A6 for 3 min. After the reaction, the residual solvent was fully washed with water to obtain a separation membrane B6.
[0140] Example 7
[0141] (1) Step (1) was carried out in the same manner as in Example 1, except that "adding 0.4 g of dopamine" was used instead of "adding 2 g of dopamine", to obtain separation membrane B7.
[0142] Example 8
[0143] (1) Step (1) was carried out in the same manner as in Example 1, except that “polymerization reaction was carried out for 3 h” was used instead of “polymerization reaction was carried out for 24 h” to obtain separation membrane B8.
[0144] Comparative Example 1
[0145] The method of Example 1 was followed, except that there was no support layer, and a complete membrane with self-supporting mechanical strength could not be obtained.
[0146] Comparative Example 2
[0147] The process was carried out in the same manner as in Example 1, except that step (1) was not performed, to obtain a separation membrane D2.
[0148] Comparative Example 3
[0149] The process was carried out in the same manner as in Example 1, except that step (2) was not performed, to obtain separation membrane D3.
[0150] The performance parameters of the separation membrane tested are shown in Table 1.
[0151] Table 1
[0152]
[0153] At 25°C and 0.1 MPa, the CO2 flux and the separation coefficient of CO2 and N2 of the test separation membrane are shown in Table 2.
[0154] Table 2
[0155] serial number <![CDATA[CO2 flux (GPU)]]> <![CDATA[Separation coefficient of CO2 and N2]]> B1 423 44 B2 572 27 B3 720 68 B4 680 54 B5 600 55 B6 319 20 B7 554 23 B8 503 31 D1 - - D2 286 17 D3 6159 2.3
[0156] It can be seen from the results in Table 1 and Table 2 that the separation membrane of the present invention has a more excellent CO2 flux and a higher separation selectivity of CO2 and N2.
[0157] Comparing Example 1 with Comparative Example 1, it can be seen that a separation membrane without a support layer cannot exist; comparing Example 1 with Comparative Example 2, it can be seen that the CO2 flux of the separation membrane without an intermediate layer is low, and the separation selectivity of CO2 and N2 is poor; comparing Example 1 with Comparative Example 3, it can be seen that the CO2 flux of the separation membrane without a functional layer can increase sharply, but the separation selectivity of CO2 and N2 is very poor and cannot meet practical applications.
[0158] Furthermore, a comparison between Example 1 and Examples 3-5 shows that when the amino polymer is a dopamine copolymer, the CO2 flux and the separation coefficient of CO2 and N2 are better than when the amino polymer is a dopamine homopolymer; a comparison between Example 1 and Example 7 shows that the amount of dopamine used will affect the CO2 flux of the separation membrane and the gas selectivity of CO2 and N2; a comparison between Example 1 and Example 8 shows that the specific polymerization reaction conditions can produce a smooth and flat intermediate layer, which is conducive to modifying the functional layer on its upper surface, and the separation membrane obtained can have both high CO2 flux and separation selectivity of CO2 and N2.
[0159] The preferred embodiments of the present invention have been described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, various simple variations of the technical solution of the present invention may be made, including combining the various technical features in any other appropriate manner. These simple variations and combinations should also be regarded as disclosed in the present invention and fall within the scope of protection of the present invention.
Claims
1. A separation membrane, characterized in that: The separation membrane comprises a support layer, an intermediate layer and a functional layer stacked in sequence; Wherein, the material constituting the intermediate layer includes amino polymer.
2. The separation membrane according to claim 1, wherein Based on the total amount of the amino polymer, the N content in the amino polymer is 3-45wt%, preferably 6-12wt%; Preferably, the theoretical weight average molecular weight of the amino polymer is 300-50000Da, preferably 400-10000Da; Preferably, the amino polymer is selected from homopolymers and / or copolymers of dopamine; Preferably, the amino polymer is selected from at least one of polydopamine, dopamine-ethylenediamine copolymer, dopamine-diethylenetriamine copolymer, dopamine-triethylenetetramine copolymer, dopamine-tetraethylenepentamine copolymer, dopamine-polyethyleneimine copolymer, dopamine-ethylenediamine-polyethyleneimine copolymer, dopamine-diethylenetriamine-polyethyleneimine copolymer, dopamine-triethylenetetramine-polyethyleneimine copolymer and dopamine-tetraethylenepentamine-polyethyleneimine copolymer; preferably at least one of polydopamine, dopamine-polyethyleneimine copolymer and dopamine-triethylenetetramine copolymer.
3. The separation membrane according to claim 1 or 2, wherein The material constituting the support layer is selected from at least one of polysulfone, polyethersulfone, polyacrylonitrile and polyvinylidene fluoride; Preferably, the weight average molecular weight of the material constituting the support layer is 1000-500000Da, preferably 2500-150000Da; Preferably, the support layer has a porous structure; Preferably, the porosity of the support layer is >10%, preferably 25-75%; Preferably, the average pore size of the support layer is 1-10000 nm, preferably 5-500 nm.
4. The separation membrane according to any one of claims 1 to 3, wherein The thickness of the support layer is 20-500 μm, the thickness of the intermediate layer is 10-500 nm, and the thickness of the functional layer is 10-1100 nm; Preferably, the thickness of the support layer is 60-150 μm, the thickness of the intermediate layer is 50-300 nm, and the thickness of the functional layer is 50-400 nm; Preferably, the average pore size of the separation membrane is 0.1-1 nm, preferably 0.2-0.5 nm.
5. The separation membrane according to any one of claims 1 to 4, wherein The material constituting the functional layer is at least one selected from polyamide and polyester.
6. The separation membrane according to any one of claims 1 to 5, wherein The CO2 flux of the separation membrane is ≥300 GPU, preferably ≥400 GPU; Preferably, the separation selectivity of CO2 and N2 of the separation membrane is ≥20, preferably ≥30.
7. A method for preparing a separation membrane, characterized in that: The method comprises: (1) in the presence of an additive, polymerizing a reaction solution containing dopamine or dopamine and an amino group-containing reactant on the surface of a support layer to prepare an intermediate layer containing an amino polymer; (2) The separation membrane is obtained by interfacial polymerization of the oil phase monomers in the oil phase solution and the water phase monomers in the water phase solution on the intermediate layer.
8. The preparation method according to claim 7, wherein: In step (1), an additive is added to adjust the pH of the polymerization reaction to 7.5-10, preferably 8.5-10; Preferably, the additive comprises additive A, or additive A and additive B, wherein additive A is selected from sodium hydroxide and / or tris(hydroxymethyl)aminomethane, and additive B is selected from at least one of hydrochloric acid, sodium dihydrogen phosphate and potassium dihydrogen phosphate; Preferably, the amino group-containing reactant is selected from amino group-containing monomers and / or amino group-containing polymers; Preferably, the amino-containing monomer is selected from at least one of ethylenediamine, diethylenetriamine, triethylenetetramine and tetraethylenepentamine; Preferably, the amino group-containing polymer is selected from polyethyleneimine; Preferably, the weight average molecular weight of the polyethyleneimine is preferably 500-2000Da, preferably 600-1800Da; Preferably, in the reaction solution, the concentration of dopamine is 0.1wt%-5wt%, preferably 0.5wt%-2wt%; Preferably, in the reaction solution, the concentration of the amino-containing reactant is 0-5wt%, preferably 0.2wt%-2wt%; Preferably, when dopamine and the amino-containing reactant are polymerized, the weight ratio of the dopamine to the amino-containing reactant is 1:10 or less, preferably 1:1.5 or less; Preferably, the reaction time of the polymerization reaction is 2-48 h, preferably 5-24 h; the reaction temperature of the polymerization reaction is 0-50°C, preferably 20-35°C.
9. The preparation method according to claim 7 or 8, wherein: In step (2), in the aqueous phase solution, the concentration of the aqueous phase monomer is 1wt%-4wt%, preferably 2wt%-4wt%; Preferably, in the oil phase solution, the concentration of the oil phase monomer is 0.05wt%-0.5wt%, preferably 0.05wt%-0.15wt%; Preferably, the weight ratio of the aqueous phase monomer to the oil phase monomer is 2-40:1, preferably 5-15:1; Preferably, the oil phase monomer is selected from at least one of trimesoyl chloride, isophthaloyl chloride, 1,4-dichlorobenzyl and 3,3,4,4-biphenyltetrachloride; preferably trimesoyl chloride; Preferably, the aqueous phase monomer is selected from amino compounds and / or hydroxyl compounds; Preferably, the amino compound is selected from at least one of m-phenylenediamine, piperazine, ethylenediamine, triethylenetetramine, tetraethylenepentamine, 1,4-cyclohexanediamine, 1,3-diamino-2-methylpropane, bis(2-aminoethyl) ether, ethylene glycol bis(2-aminoethyl) ether, diethylene glycol di(3-aminopropyl) ether, 1,4-butanediol bis(3-aminopropyl) ether and 1,4-bis(3-aminopropyl)piperazine, preferably m-phenylenediamine and / or piperazine; Preferably, the hydroxy compound is selected from at least one of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin, preferably β-cyclodextrin; Preferably, the oil phase solution further comprises an oil phase solvent, and the oil phase solvent is selected from at least one of n-hexane, n-heptane and isoparaffin; Preferably, the isoparaffin is selected from Iospar G and / or Isopar E; Preferably, the time of the interfacial polymerization reaction is 0.5-60 min, preferably 0.5-3 min, and the temperature of the interfacial polymerization reaction is 15-50°C, preferably 25-50°C.
10. The preparation method according to any one of claims 7 to 9, wherein: Step (1) further comprises: washing the prepared amino polymer intermediate layer with water; Preferably, the cleaning time is ≥5 h, preferably ≥12 h.
11. The separation membrane obtained by the preparation method according to any one of claims 7 to 10.
12. Use of the separation membrane according to any one of claims 1 to 6 and claim 11 in CO2 separation.
Citation Information
Patent Citations
PEBA (Polyether block amide) composite film as well as preparation method and application thereof
CN103657458A
Membranes for gas separation
CN111225729A
AI-based turbo compressor safety management system
KR102594592B1